Effects of Two Disinfectants and Two Growth Regulators on in vitro Propagation of Smooth Cayenne and Sugarloaf Cultivars of Pineapple (Ananas comosus (L) Mill var. comosus) - AGBIDINOUKOUN, ARNAUD (My University, 2017)
Pineapple is the first fruit crop that greatly contributes to poverty reduction for population in Benin. However, the lack of plant material is the main factor that limits field extension. The aim of this work was to optimize the production of plant material for the two pineapple cultivars by tissue culture technique. Disinfection of the buds was evaluated by using antibiotics (gentamicin at 300 mg/l for 12 hours), and disinfectants (sodium hypochlorite and mercuric chloride) at different doses and immersion duration. Axillary buds of crown were seeded on Murashige and Skoog medium (MS) supplemented with agar (0.8%). Benzylaminopurine (BAP) was tested at different concentrations (5 mg/l and 10 mg/l) or combined with naphthalene acetic acid (NAA) (4.5 mg/l BAP + 0.7 mg/l NAA). Six to eight weeks after initiation, buds were transferred to MS medium supplemented with 1 mg/l BAP + 40 mg/l adenine sulfate. The lowest infection rate (26.07%) was recorded by 15% of Sodium hypochlorite when buds were immersed for 5 min. The best bud burst rate was obtained on BAP combined with NAA (65.09%) with Sugarloaf (64.95%). After the first subculture, an average of 12.70 and 15.30 shoots per plantlet were obtained respectively for Smooth Cayenne and Sugarloaf. The number of rooted plantlets and the length of roots varied depending on the cultivar.
Keywords: Pineapple suckers; Disinfection; in vitro micropropagation; Adenine sulphate; Benzylaminopurine; Naphthalene acetic acid